All about investing in gold the easy way to get started - Jagerson, John; Hansen, S. Wade (New York McGraw-Hill, 2011)
Describes all the investible gold products, explains the fundamentals of investing in gold, and reveals techniques for implementing gold into an overall investing strategy.
Includes index.
Keywords: Gold; Investments